Implementation of Finite State Machine Models on the Artificial Intelligence System of Characters in The Game "MMORPG" using RPG Maker - Tengku Syahdina Riyan; Pardede, A M H; Manik, Fuzy Yustika (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
Technological developments are the main drivers of global social, economic, and cultural change, including in the rapidly growing gaming industry. The Role-Playing Game (RPG) genre, in which players portray characters in the game's story, is gaining popularity. The application of FSM Models and AI technology in character development and RPG game interaction not only resulted in exciting entertainment, but also inspired similar uses in various fields. With AI, characters interact dynamically with players and environments, and FSM Models govern complex character behavior, the game experience is even more immersive. RPG Maker, one of the popular engines, simplifies the process of creating RPG games with an easy user interface. The implementation of the FSM Model is done through events and switches, directing storylines and character situations with structured logic. This study analyzes the application of FSM Model in MMORPG RPG games. Through the design, testing, and analysis stages, FSM proved effective in creating games that combine entertainment with learning. This game invites players to look for requirements and challenges to proceed to the next level. The result is an MMORPG game played on a PC with a Windows operating system, providing an educational and entertaining gaming experience.